2000
DOI: 10.1146/annurev.nutr.20.1.153
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Vitamin B2 (Riboflavin)

Abstract: The biosynthesis of one riboflavin molecule requires one molecule of GTP and two molecules of ribulose 5-phosphate as substrates. The imidazole ring of GTP is hydrolytically opened, yielding a 4, 5-diaminopyrimidine which is converted to 5-amino-6-ribitylamino-2, 4(1H,3H)-pyrimidinedione by a sequence of deamination, side chain reduction and dephosphorylation. Condensation of 5-amino-6-ribitylamino-2,4(1H,3H)-pyrimidinedione with 3, 4-dihydroxy-2-butanone 4-phosphate obtained from ribulose 5-phosphate affords … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
183
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(196 citation statements)
references
References 86 publications
2
183
0
2
Order By: Relevance
“…The genes obtained from the three strains were sequenced and compared with the previously reported sequence of RIB3. 2 The sequences of the D273-10B/A21 and W303-1A genes were identical to the sequence number reported in GenBank™. The rib3 gene isolated TABLE II Respiratory activities of mitochondria Mitochondria were isolated from the parental wild type strain D273-10B/A21 and from the rib3 mutant E280 grown in YPGal and in YPGal supplemented with 25 g/ml riboflavin.…”
Section: Fig 1 Phenotype Of E280supporting
confidence: 62%
See 2 more Smart Citations
“…The genes obtained from the three strains were sequenced and compared with the previously reported sequence of RIB3. 2 The sequences of the D273-10B/A21 and W303-1A genes were identical to the sequence number reported in GenBank™. The rib3 gene isolated TABLE II Respiratory activities of mitochondria Mitochondria were isolated from the parental wild type strain D273-10B/A21 and from the rib3 mutant E280 grown in YPGal and in YPGal supplemented with 25 g/ml riboflavin.…”
Section: Fig 1 Phenotype Of E280supporting
confidence: 62%
“…This region of the insert contains RIB3, a gene of chromosome IV, previously shown to code for DHBP synthase (3). This enzyme catalyzes the conversion of ribose-5-phosphate to 3,4-dihydroxy-2-butanone-4-phosphate, an early precursors in riboflavin synthesis (2). The failure of pG164/ ST31 and pG164/ST32, each containing different halves of RIB3, to restore respiration confirmed the correct identification of the gene.…”
Section: Phenotype Of E280 and Identification Of The Mutant Gene-mentioning
confidence: 80%
See 1 more Smart Citation
“…Bacher et al [15,16] found that riboflavin biosynthesis requires the precursor's guanosine 5′-triphosphate (GTP) and ribulose 5-phosphate. The first step of the GTP-dependent branch of the biosynthetic pathway is encoded by ribA in E. coli.…”
Section: Riboflavin Biosynthesismentioning
confidence: 99%
“…GTP cyclohydrolase II (EC 3.5.4.25) (GCHII) 3 catalyzes the first step in the riboflavin biosynthetic pathway, leading to the formation of flavin nucleotide coenzymes that are utilized for a range of enzymatic reactions (1). GCHII catalyzes the conversion of GTP to 2,5-diamino-6-␤-ribosyl-4(3H)-pyrimidinone 5Ј-phosphate (DARP) (Scheme 1), the substrate for diaminohydroxyphosphoribosylaminopyrimidine deaminase.…”
mentioning
confidence: 99%